Teachers’ science camp experiences in southern Chile: Strengthening teacher identity and continuing education - Silva, Marta; Parra, Michel; Reyes-Arriagada, Ronnie; Brito, Jennifer (LUMAT: International Journal on Math, Science and Technology Education, 2021)
Science camps for teachers have been held in Chile for several years and are recognized as important opportunities for continuing education, but they have been largely ignored as instances for impactful reflection on teacher self-assessment and identity. This article presents the analysis of teacher experiences at a science camp held in southern Chile called “Explora Va!”, which was designed not just as an instance for continuing education for teachers in scientific contents but also for individual and collaborative reflection aimed at strengthening educators’ skills as agents of change in their institutions. The question of this study was: how do the participants represent their teacher identities based on their experiences at the “Explora Va!” Camp? Using a qualitative approach, the results of the analysis of narratives from teachers’ camp journals are reported here. The narratives from these journals provide an account of two dimensions, personal and contextual, where the importance of the teaching profession and science teaching were explored beyond conventional disciplinary limits. Collaboration, innovation, and personal and professional growth at the camp served to signify and resignify professional identities based on common elements but attending to the particular circumstances and unique backgrounds of each teacher.